2020
DOI: 10.1371/journal.ppat.1008664
|View full text |Cite
|
Sign up to set email alerts
|

AHR is a tunable knob that controls HTLV-1 latency-reactivation switching

Abstract: Establishing latent infection but retaining the capability to reactivate in certain circumstance is an ingenious tactic for retroviruses to persist in vivo while evading host immune surveillance. Many evidences indicate that Human T-cell leukemia virus type 1 (HTLV-1) is not completely silent in vivo . However, signals that trigger HTLV-1 latency-reactivation switching remain poorly understood. Here, we show that aryl hydrocarbon receptor (AHR), a ligand-activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
(64 reference statements)
1
13
0
Order By: Relevance
“…Our study uncovers that an interruption of the AHR pathway results in enhanced antiviral resistance in a type I IFN-independent manner. These findings are consistent with recent studies demonstrating that AHR signaling can promote infections by several viruses, including HSV-1 ( 15 , 18 , 22 , 25 ). Strikingly, novel research showed that an AHR inhibitor not only eliminates detrimental damage in respiratory function caused by IFN-β or IFN-γ but also ameliorates lung pathology caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in hACE2-transgenic mice ( 33 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study uncovers that an interruption of the AHR pathway results in enhanced antiviral resistance in a type I IFN-independent manner. These findings are consistent with recent studies demonstrating that AHR signaling can promote infections by several viruses, including HSV-1 ( 15 , 18 , 22 , 25 ). Strikingly, novel research showed that an AHR inhibitor not only eliminates detrimental damage in respiratory function caused by IFN-β or IFN-γ but also ameliorates lung pathology caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in hACE2-transgenic mice ( 33 ).…”
Section: Discussionsupporting
confidence: 93%
“…It also has been reported that HIV-1 infection and reactivation are positively correlated with AHR activation ( 24 ). The binding of activated AHR to the human T-cell lymphotropic virus type 1 (HTLV-1) long terminal repeat (LTR) dioxin response element (DRE) site has been shown to drive HTLV-1 plus-strand transcription, which is critical for viral reactivation and replication ( 25 ). Human CMV (HCMV) infection led to elevated levels of kynurenine, which is an endogenous AHR ligand, and knockdown or inhibition of AHR with chemicals decreased viral RNA levels and ameliorated RNA expression, which are associated with the cell cycle and blocked in CMV infection ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The factors that regulate the spontaneous onset of expression of the provirus are not fully understood, but include the proviral integration site [58], cell stress [20, 59], AHR signaling [60], and ubiquitinylation of histone 2A lysine 119 by polycomb repressive complex 1 (PRC1) [61]. RING1 , RYBP and KDM2B are members of the non-canonical PRC1 (ncPRC1) [62] and their expression was up-regulated during the burst (Fig 7).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, great progress has been made in this field. We found that the aryl hydrocarbon receptor (AHR) was a tunable knob and controlled HTLV-1 latency-reactivation switching [ 3 ], and the activation of Notch1 signaling by HTLV-1 Tax promoted proliferation of adult T cell leukemia cells [ 4 ]. T cell acute lymphoblastic leukemia (T-ALL), a malignant hematologic disease characterized by the uncontrolled proliferation of immature T-lymphoid cells, is more frequently reported in pediatric patients and hard to cure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%